The complexities of statistical measurements of new social processes: a system of Downshifting indicators (Nexo Revista Científica, 2021)
In the 21st century, new social processes that used to be considered illogical, unusual, and even impossible in the recent past are becoming increasingly widespread. Downshifting implying deliberate rejection of the benefits of modern civilization should undoubtedly be viewed as one of such processes. In various countries and corners of the planet, the scale of the development of downshifting has now acquired such a great magnitude that acting like nothing is happening would be both impossible and wrong. Meanwhile, an unequivocal perception of downshifting as an exclusively favorable or unfavorable process has not yet formed in society. In this context, attempts at measuring and statistically evaluating the various parameters of downshifting draw great interest from the point of science and practice. However, it has to be admitted that statistical science somewhat lags behind the present demands and needs of society since the system of downshifting indicators providing its comprehensive characteristic and allowing for a relatively clear answer to the question of the actual role of such an unusual social process has not yet been developed. In this context, the present article examines the specific characteristics of the quantitative analysis of downshifting, analyses various approaches to creating a downshifting statistics indicator system, and presents the authors’ propositions considering the structure and components of the system of downshifting indicators allowing not only comprehensively demonstrating the scale, structure, distribution, and intensity of this process, but also addressing its socio-economic results and consequences.